Understanding learning anxiety and mental health of final year students: A qualitative study - Berutu, Rohiyati; Mutiawati, Mutiawati (Universitas Negeri Yogyakarta, 2023)
Anxiety is a feeling of fear, excessive worry, and unpleasant feelings that assume that something bad will happen. Learning anxiety can also be interpreted as a feeling of worry while an individual experience an under pressure situation and inability to complete something. It is normal for students to have excessive anxiety during the learning process, due to the many internal and external factors that occur in their environment. The research method used was descriptive qualitative research. The research instruments used were interviews and observations. The researcher conducted observations at the Universitas Islam Negeri Sumatera Utara and obtained three final year students who experienced excessive learning anxiety, which could disrupt their learning activities. This greatly affects the students' mental health. Therefore, the researchers aim to examine the impact of excessive learning anxiety on students' mental health. Among the three students, two students experienced excessive learning anxiety, which had an impact on their physical and mental health. These two students experienced symptoms of shortness of breath and sleep disturbances that interfered with their daily activities. While one student merely had general learning anxiety in the form of fear of something bad happening, which is often experienced by students in general.